1998
DOI: 10.1016/s0378-1097(98)00359-0
|View full text |Cite
|
Sign up to set email alerts
|

The GroEL-like protein from Campylobacter rectus: immunological characterization and interleukin-6 and -8 induction in human gingival fibroblast

Abstract: The native GroEL-like protein was purified from Campylobacter rectus, a putative periodontal pathogen, by affinity chromatography on ATP-agarose followed by high performance liquid chromatography on Superose 6. The purified 64-kDa protein (denatured form of GroEL-like protein) was immunoreactive by SDS-PAGE and Western immunoblotting with the monoclonal antibody directed against heat shock protein 60 of human origin. The native GroEL-like protein stimulated both interleukin-6 (IL-6) and IL-8 secretion by a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 17 publications
1
41
1
Order By: Relevance
“…Bacterial GroEL heat shock proteins are a conserved group of chaperonins whose function to mediate protein folding has made them widely essential to resist various stressors such as extreme temperatures or nutrient limitation (164,265,348). Interestingly, although no member of the GroEL family bears any discernible secretion signal, overwhelming evidence indicates that surface-exposed or secreted GroEL plays a key role in the infection strategies of many bacterial pathogens (35,181,184; reviewed in reference 174). As an example, the corresponding homolog of Legionella pneumophila is known to be displayed on the bacterial surface, where it promotes an invasive phenotype, and the same protein apparently manipulates cellular trafficking, cytoskeleton, and signaling once it is released inside the eukaryotic host cell (recently reviewed in reference 153).…”
Section: The Primary Nichementioning
confidence: 99%
“…Bacterial GroEL heat shock proteins are a conserved group of chaperonins whose function to mediate protein folding has made them widely essential to resist various stressors such as extreme temperatures or nutrient limitation (164,265,348). Interestingly, although no member of the GroEL family bears any discernible secretion signal, overwhelming evidence indicates that surface-exposed or secreted GroEL plays a key role in the infection strategies of many bacterial pathogens (35,181,184; reviewed in reference 174). As an example, the corresponding homolog of Legionella pneumophila is known to be displayed on the bacterial surface, where it promotes an invasive phenotype, and the same protein apparently manipulates cellular trafficking, cytoskeleton, and signaling once it is released inside the eukaryotic host cell (recently reviewed in reference 153).…”
Section: The Primary Nichementioning
confidence: 99%
“…Despite being highly homologous between prokaryotic and eukaryotic cells, hsp60s are strongly immunogenic, and immune responses to microbial hsp60s are speculated to initiate chronic inflammatory diseases in which autoimmune responses to human hsp 60 may be central to pathogenesis (16). Major periodontopathic bacteria such as Porphyromonas gingivalis (13,19), Actinobacillus actinomycetemcomitans (21), Fusobacterium nucleatum (37), Prevotella intermedia (37), Bacteroides forsythus (37), and Campylobacter rectus (11) are reported to produce hsp's homologous to Escherichia coli GroEL. We have previously demonstrated that the frequency of seropositivity and titers of antibodies to human hsp60 and P. gingivalis GroEL were significantly higher in periodontitis patients than in periodontally healthy control subjects (29).…”
mentioning
confidence: 99%
“…In addition to participating in bacterial adhesion, HSPs have been shown to have cell-cell signaling properties and are able to modulate the activity of host cells. The actions of bacterial HSPs on host cells include inducing the synthesis of pro-inflammatory cytokines (74,75). HSPs have also been reported to promote apoptosis and this effect is likely to inhibit host antibacterial responses (73).…”
Section: Heat-shock Proteinsmentioning
confidence: 99%